A model of price correlations between clean energy indices and energy commodities. (3rd April 2022) - Kanamura, Takashi
ABSTRACT: We propose a new supply and demand-based correlation model of clean energy indices and energy prices with the influence of energy on clean energy business including renewables. Empirical studies estimate the model parameters using the stock indices and energy prices including S&P Global Clean Energy Index (GCE), Wilderhill Clean Energy Index (ECO), S&P/TSX Renewable Energy and Clean Technology Index (TXCT), S&P 500, WTI crude oil prices, and Henry Hub (HH) natural gas prices. Results show the correlations between GCE or ECO and WTI crude oil or HH natural gas prices are positive and an increasing function of the corresponding energy prices. It seems reasonable because the values of renewable energy businesses, which sell electricity in the spot market, are enhanced by the increase in energy prices, considering that electricity spot prices increase in line with energy prices. In contrast, results show the correlations between S&P 500 and WTI or HH prices are still positive but a decreasing function of the energy prices. This sharp contrast may come from the fact that the S&P 500 listed companies' businesses can be damaged by high energy prices while not applicable to GCE and ECO companies. Regarding TXCT, the correlations with WTI are positive and are a decreasing function of WTI while those with HH tend to be positive and are an increasing function of HH. It may suggest that TXCT is not fully functioning but still developing as a clean energy index, taking into account the results of GCE and ECO.